1998
DOI: 10.1093/jn/128.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Orally Fed Digalactosyldiacylglycerol Is Degraded during Absorption in Intact and Lymphatic Duct Cannulated Rats

Abstract: Membrane lipids of green plants digalactosyldiacylglycerol (DGalDG) and monogalactosyldiacylglycerol (MGalDG) are hydrolyzed in vitro by human duodenal contents, pancreatic juice and bile salt stimulated lipase and guinea pig and rat pancreatic lipase-related protein 2 to free fatty acids, di- and monogalactosylmonoacylglycerols and water soluble galactose-containing compounds. The fate of intermediate products is unknown. We have investigated the digestion and absorption of DGalDG in rats. [3H]- and [14C]-lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 15 publications
0
14
1
Order By: Relevance
“…Although previous studies indicated that oral galactolipids are degraded and might not to be absorbed intact by rats (30) and are hydrolyzed by human pancreatic enzymes and duodenal contents (31), suggesting a low bioavailability of the unchanged form of dLGG and its derivatives, this study shows that i.p. administration of dLGG can significantly inhibit melanoma growth without mortality or body weight loss.…”
Section: Cancer Researchcontrasting
confidence: 68%
“…Although previous studies indicated that oral galactolipids are degraded and might not to be absorbed intact by rats (30) and are hydrolyzed by human pancreatic enzymes and duodenal contents (31), suggesting a low bioavailability of the unchanged form of dLGG and its derivatives, this study shows that i.p. administration of dLGG can significantly inhibit melanoma growth without mortality or body weight loss.…”
Section: Cancer Researchcontrasting
confidence: 68%
“…In rats orally fed with DGDG, the fatty acids generated after hydrolysis were shown to be reesterified into triglycerides and phospholipids in the enterocytes and then transported by triglyceride-rich lipoproteins [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few studies have suggested that some of these glycolipids are digested and not absorbed in an in vivo rat model [19,20], in vitro human pancreatic lipolytic enzyme, and duodenal contents model [21].…”
Section: Introductionmentioning
confidence: 99%